PEMBELAJARAN MATEMATIKA DENGAN MENGGUNAKAN MODEL ASSURE PADA MATERI LOGARITMA - Danil, Fransisco; Amorie, Jean; Cahyadi, Rahman (JURNAL e-DuMath, 2019)
ABSTRACTTeacher centered learning patterns cause drowsiness, lack of enthusiasm, and many who do not pay attention.This lack of learning innovation is thought to cause low student learning outcomes.To overcome this problem, one of them is by applying the ASSURE model. The purpose of this study is to find out (1) there are differences in the average student mathematics learning outcomes with learning using the ASSURE model with students' mathematics learning outcomes with direct learning models. (2) the average mathematics learning outcomes of students who learn using the ASSURE model are higher than students whose learning uses direct learning. Furthermore, the data were analyzed using the statistical test t, because the data is homogeneous and comes from a population that is normally distributed. From the results of the data analysis it can be concluded that there are differences in the average student learning outcomes using ASSURE model learning with direct learning and the average learning outcomes of the ASSURE model is higher than the direct learning model.Keywords: ASSURE Learning Model, Learning Outcomes